Fostering Noble Ethics for Future Generations: Building Character in SB Kampung Baru's Students - Siti Ainun Fadilah; Mega Puspaningrum; Reyza Wulandari; Naufal Ishartono; Toni Ahmad Subekti; Miftakhul Huda; Muhammad Fahmi Johan Syah (Asosiasi Lembaga Pendidikan Tenaga Kependidikan Peguruan Tinggi Muhammadiyah dan Aisyiyah, 2023)
Ramadan Pesantren is one of the programs conducted by the 6th cohort of KKN DIK International students and was held on March 26-27, 2023, during the month of Ramadan. The objective of this program was to address issues and provide information related to religious matters, enhancing the students' knowledge at Sanggar Bimbingan Kampung Bharu. The activities in Ramadan Pesantren were not limited to religious studies alone; they also included teamwork exercises, concentration training, physical conditioning, and various other activities aimed at fostering a sense of togetherness. The results of the Ramadan Pesantren activities at Sanggar Bimbingan Kampung Bharu showed that the majority of students comprehended the material and enjoyed the activities, finding them engaging, enjoyable, and beneficial for the participating students.